Influencia del % de vanadio sobre el límite de fluencia, resistencia a la tracción y % de alargamiento del acero astm a615 de 1 3/8” en la empresa siderperu del distrito de chimbote - Lizárraga Santos, Luis Alfredo (2017)
Compliance and improving the mechanical properties of the reinforcing bar, leading to better adding ferro-alloys such as vanadium, so that the influence of % vanadium was studied on the yield strength, tensile strength and % elongation of the steel ASTM A615 1 3/8" in the SIDERPERU company in the district Chimbote, this was done by addition of a ferro-alloy of vanadium in the ladle furnace, this addition is calculated following an established procedure and that this vanadium content is within a set range. The best results from this study were obtained containing 0.026% approx. of vanadium, being the maximum limit of 534 MPa yield strength and the maximum tensile strength of 738 MPa, was when the vanadium content is 0.029% approx. and a vanadium content of 0.033% approx. the highest percentage of elongation was 21%. Within the range of 0.025% to 0.033% vanadium allowed us to meet whit the standard ASTM A615, exceeding 40 MPa the specified minimum values for the yield strength of 420 MPa and tensile strength of 620 MPa and elongation 17% on average. With this are improved the mechanical properties of the reinforcing bar ASTM A615 construction 1 3/8" in the company SIDERPERU in the district of Chimbote, using a content of vanadium as micro-alloying within a range studied and improved.